2019
DOI: 10.1111/jbi.13779
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of alpine tree lines under global warming: What explains the mismatch between tree densification and elevational upward shifts at the tree line ecotone?

Abstract: Aim: Most studies focusing on the alpine tree line responses to climate warming have used either the tree densification within the ecotone or its elevational upshift as indicators. However, it is acknowledged that the relationship between densification and upshift is spatially heterogeneous, making inferences and comparability among studies tricky. The lack of consistent empirical evidence on this potential mismatch and its drivers leads us to focus on this issue in this study. The aim was twofold: (a) to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…The rate of advanced establishment, defined as the change from establishing forest to forest within a change period is shown for the study area as a whole (b), by aspect (d) and by incline (f). Uncertainty in the estimates in panels a and b is shown at the 95% confidence intervals substantial increase in forest area, yet stasis in mean forest elevation reported here, (Figure 3) has also been observed globally including in the Khibiny Mountains, Russia (Mathisen et al, 2014), the Tibetan Plateau (Liang et al, 2011), Glacier National Park, USA (Klasner & Fagre, 2002), the Sudetes mountains, Czech Republic (Treml & Chuman, 2015) and the Pyrenees, France (Feuillet et al, 2020). In Taiwan, our findings are consistent with patterns of forest advance previously identified in field assessments by who identified that forest advance in Taiwan elevation, yet densification below the tree line and increases in the elevation of establishment in localized depressions here ( Figure 3) and elsewhere are occurring despite a lack of change in tree line position (Klasner & Fagre, 2002;Liang et al, 2011;Mathisen et al, 2014;Treml & Chuman, 2015).…”
Section: F I G U R Esupporting
confidence: 67%
See 4 more Smart Citations
“…The rate of advanced establishment, defined as the change from establishing forest to forest within a change period is shown for the study area as a whole (b), by aspect (d) and by incline (f). Uncertainty in the estimates in panels a and b is shown at the 95% confidence intervals substantial increase in forest area, yet stasis in mean forest elevation reported here, (Figure 3) has also been observed globally including in the Khibiny Mountains, Russia (Mathisen et al, 2014), the Tibetan Plateau (Liang et al, 2011), Glacier National Park, USA (Klasner & Fagre, 2002), the Sudetes mountains, Czech Republic (Treml & Chuman, 2015) and the Pyrenees, France (Feuillet et al, 2020). In Taiwan, our findings are consistent with patterns of forest advance previously identified in field assessments by who identified that forest advance in Taiwan elevation, yet densification below the tree line and increases in the elevation of establishment in localized depressions here ( Figure 3) and elsewhere are occurring despite a lack of change in tree line position (Klasner & Fagre, 2002;Liang et al, 2011;Mathisen et al, 2014;Treml & Chuman, 2015).…”
Section: F I G U R Esupporting
confidence: 67%
“…Furthermore, as temperature thresholds are passed at a given elevation, a larger area of habitat is likely to be affected by environmental change when the slope inclination is shallow (Jump, Mátyás, & Peñuelas, 2009). Therefore, in combination with an increased probability of forest establishment on shallow and concave slopes (Feuillet et al, 2020;Greenwood et al, , 2015, environmental changes lead to higher rates of (Greenwood et al, 2015). Consequently, areas that undergo establishment but do not continue to grow sufficiently to be classified as forest may exist in areas where a threshold for establishment has been surpassed, but the necessary conditions for subsequent growth are not met.…”
Section: F I G U R Ementioning
confidence: 99%
See 3 more Smart Citations